COVID-19 PANDEMIC: A STUDY ON THE RELATIONSHIP BETWEEN SOCIAL DISTANCING AND MENTAL HEALTH STATUS AMONG PEOPLE AGED 50 AND OLDER IN EUROPE - Yordanov, Vladimir (Revista Inclusiones, 2021)
Background: Many procedures and regulations have been implemented by the policymakers to control the Covid-19 pandemic expand and establish a health-oriented environment. Objectives: This paper addresses the relationship between mental health and social distance restrictions taken by the government during the Covid-19 pandemic among people aged 50 years and older in Europe. Methods: For the research are used data from the SHARE Covid-19 dataset Wave-8. The response variable is mental health measured by the level of depression and stress in a time of pandemic. The explanatory variables included in our research examine the behavior of people and the frequency of their social contacts since the Covid-19 outbreak. For our exploration, we apply logistic regression to test significance of the variables related to social distancing among all countries. Results: Social distancing measures taken by the government have an impact on the human well-being. In many of the respondents is observed a change in their behavior and outdoor activities. Reduced level in shopping, going for a walk and people gathering are part of the social policy proposed by health experts. As a result, an increased level of stress, depression and sleep disorder is observed. People who worsened their health at that time have strong correlation among the levels of stress and depression. On other hand, mental health status is examined as better to ones keeping physical contacts. Conclusion: The consequences of the epidemic lockdown measures of Covid-19, affects negatively on social life and mental health of people. A need of more flexible pandemic measures might be considered, in term of prevention and protection of the human well-being.